Pemanfaatan Sensor Suhu DHT-22, Ultrasonik HC-SR04 Untuk Mengendalikan Kolam Dengan Notifikasi Email - Siswanto; Ikin Rojikin; Windu Gata (Ikatan Ahli Informatika Indonesia (IAII), 2019)
In the case of handling rainwater reservoirs, officers are currently overwhelmed, because they have to continue to monitor changes in water level manually. This is ineffective and inefficient because officers must always be present at the location of the water reservoir. While HR is very limited. The purpose of this study is to make an application to monitor and control water levels in rainwater reservoirs with temperature & humidity sensors DHT-22, ultrasonic sensors HC-SR04 and Arduino Uno R3 microcontrollers, so that they can report quickly to staff through email notifications making it easier for staff monitor changes in water level in a rainwater reservoir remotely. This application interface is made using the Arduino programming language, for its web display using the PHP programming language and MySQL database. The results of the trial were obtained as much as 90% of users said the system created was very helpful in controlling the water level of the water reservoir and working in realtime, and as many as 10% of users said the system created was less helpful in controlling the water level of the water reservoir.